Building Employee Engagement to Achieve the Vision and Mission of Satya Negara Hospital - Deasy Nurindah Sari; Mus Aida; Rokiah Kusumapradja (Penerbit Kemala Indonesia, 2023)
This study aims to analyze the jointly significant influence of internal marketing, self-efficacy, and employee engagement on the achievement of the Vision and Mission of Satya Negara Hospital. A quantitative approach with path analysis method using the Structural Equation Modeling equation was used as the methodology of this study. The sampling technique was carried out by purposive sampling as much as 63 respondents. It is based on the number of health workers with permanent employee status at Satya Negara Hospital. The results show that Internal Marketing, Self-Efficacy, and Employee Engagement have a significant influence on the achievement of the Vision and Mission of Satya Negara Hospital. Partially, Internal marketing directly has a significant positive influence on the achievement of the Vision and Mission of the Satya Negara Hospital. Internal Marketing also has a partially significant positive effect on Employee Engagement at Satya Negara Hospital. On the other hand, Self-efficacy has a significant positive effect on Employee Engagement at Satya Negara Hospital partially. Self- efficacy directly has a significant and weak positive influence on the achievement of the Vision and Mission of the Satya Negara Hospital partially. Furthermore, Employee Engagement directly has a significant positive effect on the achievement of the Vision and Mission of the Satya Negara Hospital partially. Internal marketing indirectly has a significant positive influence on the achievement of the Vision and Mission of the Satya Negara Hospital through the variable employee engagement intervening. Self-efficacy indirectly has a significant positive effect on the achievement of the Vision and Mission of the Satya Negara Hospital through the intervening variable employee engagement. The findings of this study are that Employee Engagement acts as a partial mediation variable to provide a strong indirect influence on Self-Efficacy towards the Achievement of the Vision and Mission of Satya Negara Hospital. The managerial implication of this research is to improve the remuneration system and rewards obtained by health workers fairly and appropriately based on the individual performance of health workers.